The relation between natural and sexual selection – study case on the phenotypic characteristics that influence mate choice in a North-West Romanian human population - Sînziana Alexandra POPA-CORDUN; Alexandru N. STERMIN (Studia Universitatis Babeș-Bolyai. Biologia, 2019)
The force of sexual selection acts upon the mating process of all beings, this great force is influenced by different factors as phenotypic characteristics. Related to mate choice, in humans, recent studies have shown that, along with eye color, hair color is considered a relevant physical trait (Frost, 2006). Thereby, the purpose of this study is to reveal how these two factors influence mate choice by analyzing the hair color preference of a small population from Romania. Additionally, we explore how different types of selection influence each other and assume that both contribute in choosing a partner. In order to obtain basic data, a socio-demographic survey was addressed to adult male and female individuals. Based on their answers, disregarding the gender, a considerable number of individuals are brown-haired, as we expected from this area of the globe. Among the results obtained, the following considerations are worth mentioning: the most common hair color in Romania is brown, individuals with this trait are considered the most attractive for the opposite sex and parents’ hair color represents a predictor for future partners. These preferences are both in concordance and in contrast with natural selection. However, much more research is needed, approaching other areas such as genetics and forensics to determine how all these mechanisms, as well as others, affect the process of mating.